TRANSFORMASI MANAJEMEN STRATEGI RUMAH SAKIT DI ERA DIGITAL: DARI INOVASI KONSEPTUAL KE PRAKTIK OPERASIONAL - Abdul Gopur; Ni Luh Putu Adinda Tasya Saraswati; Purwadhi Purwadhi; Yani Restiani Widjaja (PUBLISHER ABISATYA DINAMIKA ISWARA PUBLISHING, 2026)
Digital transformation has become a crucial element in the development of hospital strategic management in the modern era. Hospitals are no longer required solely to provide clinical services but must also manage complex organizations efficiently through the use of digital technologies. This study aims to describe the concept of hospital strategic management transformation in the digital era, identify emerging forms of conceptual innovation, and analyze how these innovations are implemented in operational practices. The research employs a Systematic Literature Review (SLR) method with a qualitative descriptive approach, reviewing relevant scientific publications from the last five years. The findings indicate that conceptual innovations such as the digitalization of clinical and administrative processes, the use of data analytics, and digitally integrated service models significantly enhance operational efficiency, service quality, and evidence-based decision making. However, the implementation process faces several challenges, including limited technological infrastructure, insufficient human resource competencies, organizational resistance to change, and data security issues. The study concludes that successful digital transformation depends on the alignment between strategic vision, technological capabilities, and adaptive organizational culture. Therefore, hospitals are recommended to strengthen organizational readiness through continuous human resource development, improved digital infrastructure, and ongoing performance monitoring and evaluation.